The Influence of Teacher Skill Variety on Pupils’ Academic Performance in Tanzanian Public Primary Schools - James, Stephen; Masue, Orest; Mollel, Henry (Journal of Policy and Leadership, 2024)
Pupils in many public primary schools in Tanzania still perform poorly academically. This study examined the influence of teacher skill variety on pupils’ academic performance. The study employed a survey research design to collect data from four Local Government Authorities: Ngara, Kibondo, Tanga City and Mafinga Town and involved 95 public primary schools. The sample size included 354 teachers and (16) key informants. Purposive and, multi-stage stratified simple random sampling were employed to select participants. The data collection methods comprised questionnaires, interviews, and a documentary review. Binary logistic regression analysed quantitative data while qualitative data were analysed thematically and presented by quotations and descriptions. The findings showed that the Likelihood Ratio Chi-square values for teacher skill variety = (106.18; p <.001), implying that the teacher skill variety model had a vast and significant likelihood on pupils’ academic performance. The odd ratio of teacher skill variety = 3.22 (95% Confidence Interval [CI]; 2.29, 4.17), suggesting that the odds of high teacher skill variety were three times more likely to influence pupils' academic performance than low teacher skill variety. The marginal effect showed that teacher skill variety had a probability on pupils’ academic performance 16 per cent higher than teachers without skill variety. We concluded that skill variety enabled teachers to deliver educational material using practical skills for pupils' learning. We recommended that stakeholders collaborate with public primary schools to organise training programmes on skill variety for teachers to acquire a bundle of skills to enhance pupils’ academic performance.